Da legitimidade de textos poéticos musicados como fonte para o estudo da prosódia de tempos passados do português: O exemplo das cantigas medievais galego-portuguesas - Massini-Cagliari, Gladis [UNESP] (2014)
This work shows how information about phonological phenomena such as syllable boundaries, diphthongization, vocalic elision and primary and secondary stress positioning can be extracted from the relation between poetic and phonetic syllables, taking as an example the music and the lyrics of one Martim Codax' cantiga de amigo.